Study of vesicular mole and its outcomes (Panacea Journal of Medical Sciences, 2024)
Background: Vesicular mole is defined as the premalignant form of gestational trophoblasticneoplasia. I5-20% of complete moles and  Materials and Methods: It was a retrospective study. Approval for the study was obtained from institutional ethical committee. Data was collected from OPD, OT register and Indoor patient record file from August 2015 to August 2020. Proformas were filled. All the collected data was compiled in a master chart, analysed and outcomes of different variables under study have been expressed in the form of mean, frequencies, percentages and charts.Results: The incidence of molar pregnancy was 0.17% or 1 in 561 deliveries. Vesicular mole occurred more in the age group 16 to 25 years, was lowest in age group 31-35yrs. Vesicular mole was most common in nulliparous women. The mean gestational age of the patients at presentation was 9.4 week. Hemorrhage after suction and evacuation was seen in 26% cases needing intra and post-operative blood transfusion. 6% of patients developed thyrotoxicosis. During follow up invasive mole was diagnosed in 2 cases (6%). The case fatality rate is 2.9% in our study. 1 patient (3%) developed choriocarcinoma and died within 6months after hysterectomy and chemotherapy.Conclusions: The incidence of 1 in 561 deliveries which is higher than non-Asian countries 1/752 but lower than other Asian countries 1/387. The routine first trimester ultrasonography helps in early detection of asymptomatic women. If not followed up regularly it can be life threatening.